How teachers perceive factors that influence creativity development: Applying a Social Cognitive Theory perspective. (February 2018) - Rubenstein, Lisa DaVia; Ridgley, Lisa M.; Callan, Gregory L.; Karami, Sareh; Ehlinger, John
Abstract: This mixed methods study examined teachers' perceptions of creativity using Social Cognitive Theory factors (e.g., personal, behavioral, and environmental). When describing hindrances to creativity, teachers often discussed macro-environmental factors, yet when explaining or defining creativity, teachers often used personal and behavioral characteristics. Teachers did not seem to hold limited views on who can be creative or that creativity always results in products; however, some teachers' conceptions were too vague to guide the explicit facilitating of creativity. Compared to in-service teachers, pre-service teachers expressed more optimism in their future environmental support and lower self-efficacy for developing creative thinking. Highlights: Teachers view personal and behavioral factors as contributors to successful creativity. Teachers describe environmental factors as only hindrances to creativity. Teachers do not believe creativity is reserved for the eminent. Pre-service teachers believe their environments will support them, unlike in-service teachers.